Resiliensi Bumdes dalam Mendeteksi Fraud di Era Pandemi - Grace Phillandros Violetta; Fitriyani Fitriyani; Ika Kristianti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
BUMDes was established with the aim of improving village welfare as well as creating jobs. Fraud often still occurs in the operational activities of all organizations, including BUMDes. The most potential for fraud that appears is due to revolving fund financial irregularities. The purpose of this study was to examine the resilience ability of BUMDes to detect fraud that occurred during the pandemic. This study used a qualitative method with the object of research at BUMDes Sumilen. Respondents of this study were BUMDes administrators. The data used is primary data, which is obtained from interviews with respondents. The results of this study did not have a material impact on the current pandemic conditions. Fraud and the potential for fraud do not occur frequently. BUMDes seeks deliberation when there are deviations in their operational activities. BUMDes are expected to be more sensitive in detecting fraud risks and implementing internal controls to minimize the potential for fraud that occurs so that the purpose of establishing BUMDes can be achieved.